2012
DOI: 10.12693/aphyspola.121.1207
|View full text |Cite
|
Sign up to set email alerts
|

Spin Thermoelectric Effects in Transport through a Two-Level Quantum Dot Coupled to Ferromagnetic Leads

Abstract: We investigate spin thermoelectric eects in a two-level quantum dot attached to external ferromagnetic leads. The basic thermoelectric coecients are calculated by means of the non-equilibrium Green functions approach in the mean eld approximation for the Coulomb term. Specically, we calculate spin-dependent thermopower (spin Seebeck coecient) and the charge thermopower. These coecients measure spin and charge voltage drops across the device, respectively. Moreover, the gure of merit and its spin analog (which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It should be noticed that the discussions in literature [7,9,10] are for parallel polarization of ferromagnetic leads. Inspired by literature [11], the direction of polarizations of the ferromagnetic leads on the left and right are opposite here, and a perpendicular magnetic field is choose, namely B = 0.001U = 0.002 meV, = − = p p 0.8…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noticed that the discussions in literature [7,9,10] are for parallel polarization of ferromagnetic leads. Inspired by literature [11], the direction of polarizations of the ferromagnetic leads on the left and right are opposite here, and a perpendicular magnetic field is choose, namely B = 0.001U = 0.002 meV, = − = p p 0.8…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, Y Dubi and his fellows firstly researched the spin Seebeck effect in quantum dots (QDs) coupled to ferromagnetic leads [7]. While the direction of the magnetic field is parallel to the spin polarized direction, a non-zero spin flow would be generated with no charge current, and by adjusting the gate voltage of the QD, thermal-to-spin transformation efficiency can exceed the thermal-to-electron conversion efficiency: in 2012, Bai et al [8] ignored the magnetic field of the QDs based on the model built by Dubi et al and discussed the spin accumulation in QDs caused by thermal bias; in 2011 Wierzbicki et al [9], and in 2012 Karwacki et al [10], studied the thermal spin effect in two-level QDs. In the same year, while considering the impact of non-collinear ferromagnet leads on the thermoelectric effect of double QDs, Jun et al [11] concluded that thermal-to-spin transformation efficiency could be significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%